Dietary Inclusion of a Mixed Powder of Medicinal Plant Leaves Enhances the Feed Efficiency and Immune Function in Broiler Chickens - Roisbel Aroche; Yordan Martínez; Zheng Ruan; Guiping Guan; Samuel Waititu; Charles M. Nyachoti; Dairon Más; Shile Lan (Journal of Chemistry)
The trial was designed to determine the effect of the mixed powder of leaves of Anacardium occidentale (60%), Psidium guajava (20%), and Morinda citrifolia (20%) on growth performance, nutrient digestibility, and immunoglobulin concentration in broiler chickens. A total of 80 one-day-old Ross 308 broiler chickens were randomly assigned to two dietary treatments from days 1 to 21 of age, with 8 replicates by treatments and 5 birds per replicate. Treatments consisted of a control diet (T0) and the dietary inclusion of 0.5% of mixed powder of medicinal plant leaves (T1). The inclusion of herbs decreases the feed intake (FI) and feed conversion ratio (FCR; P<0.05) in week 2 and in the period studied (1–21 days) compared with T0 but did not modify (P<0.05) the body weight (BW) and average gain (AG). Also, the mixed powder has no influence (P>0.05) on nutrient digestibility and IgA concentration; however, the IgG concentration increased by the effect of this experimental treatment. The results allow recommending the dietary inclusion of mixed powder of medicinal plant leaves as an alternative for obtaining acceptable performance in broilers.